Legal Arrangement for Household Workers: A Case Study of Plasma Fake Eyelashes Industry in Labor Law Perspective - Susilo Wardani; Ari Hernawan (Fakultas Hukum Universitas Muhammadiyah Magelang, 2021)
This study analyzes legal protection for domestic workers in the plasma fake eyelashes industry in Kabupaten Purbalingga from a labor law perspective. The method used in this study is juridical empirical. The data used in this study consisted of primary data, secondary data. Primary data were obtained from a field study conducted in Bojongsari District and the plasma fake eyelashes industry in Purbalingga Regency. Secondary data is obtained from primary legal materials in the form of laws and regulations relevant to the topic under study. According to the employment law, the research result shows that the legal protection of homeworkers in the Plasma hair industry in Purbalingga faced a significant challenge. Although it is covered in law 13 of 2003, it does not accept the right and protection as stipulated in the law on wages, employment contracts, freedom of Union and assembly, working hours, occupational safety and health, and social security. With these issues, home workers are very vulnerable and hold poor positions; therefore, particular actions are needed to encourage the protection and fulfillment of their fundamental rights. Strategic policies need to be carried out that recognizes the existence of home workers. These policies need to be incorporated into national statistical data and legislation as an affirmative step taken by the Indonesian Government. Furthermore, the Government needs to develop home worker protection policies that include their fundamental rights. The Government needs to establish a mandatory minimum health and worker protection scheme not to be a burden